2007
DOI: 10.1111/j.1462-2920.2007.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Global phylogeography of marine Synechococcus and Prochlorococcus reveals a distinct partitioning of lineages among oceanic biomes

Abstract: Marine cyanobacteria of the genera Prochlorococcus and Synechococcus are important contributors to global primary production occupying a key position at the base of marine food webs. The genetically diverse nature of each genus is likely an important reason for their successful colonization of vast tracts of the world's oceans, a feature that has led to detailed analysis of the distribution of these genetic lineages at the local and ocean basin scale. Here, we extend these analyses to the global dimension, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

80
538
10
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 414 publications
(631 citation statements)
references
References 52 publications
80
538
10
3
Order By: Relevance
“…It has been shown that some prokaryotes, such as the SAR11 clade (Morris et al 2002), occur globally, whereas others, like the RCA (Roseobacter clade affiliated) phylogenetic cluster, exhibit distinct distribution patterns and appear to reflect features of distinct marine biomes or even regional systems (Selje et al 2004, Pommier et al 2005. Cyanobacterial lineages also distribute differentially across marine biomes (Zwirglmaier et al 2008). In fact, analysis of the metagenomic libraries of samples from the northwest Atlantic and eastern tropical Pacific 'Sorcerer II' global ocean sampling expedition revealed distinct regional patterns of the phylogenetic diversity (richness) of the prokaryotic communities (Rusch et al 2007).…”
Section: Refined Functional and Regional Resolutionmentioning
confidence: 99%
“…It has been shown that some prokaryotes, such as the SAR11 clade (Morris et al 2002), occur globally, whereas others, like the RCA (Roseobacter clade affiliated) phylogenetic cluster, exhibit distinct distribution patterns and appear to reflect features of distinct marine biomes or even regional systems (Selje et al 2004, Pommier et al 2005. Cyanobacterial lineages also distribute differentially across marine biomes (Zwirglmaier et al 2008). In fact, analysis of the metagenomic libraries of samples from the northwest Atlantic and eastern tropical Pacific 'Sorcerer II' global ocean sampling expedition revealed distinct regional patterns of the phylogenetic diversity (richness) of the prokaryotic communities (Rusch et al 2007).…”
Section: Refined Functional and Regional Resolutionmentioning
confidence: 99%
“…However, noteworthy is that all three sites have comparatively high chlorophyll a concentrations (ranging between 0.28 and 1.37 mg m À 3 ) and moderate species richness determined by the Margalef index. Even so, resolving the combination of parameters responsible for structuring the PPE community is likely to be much more complex than for picocyanobacterial communities (Zwirglmaier et al, 2008) given the differences of taxonomic resolution between groups (picocyanobacteria have been studied at the genera level).…”
Section: Ppe B-diversitymentioning
confidence: 99%
“…Previous investigations of Prochlorococcus biogeography have characterized phylogenetic diversity using specific genetic markers that reflect genome content to an unknown extent (Bouman et al, 2006;Johnson et al, 2006;Zwirglmaier et al, 2008). Metagenomics has also been employed to examine Prochlorococcus genomic diversity at smaller regional scales (Hewson et al, 2009;Rusch et al, 2010;Thompson et al, 2013) but not yet on a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Within the group, there are multiple phylogenetically distinct lineages and the distribution of this diversity has been linked to environmental factors, such as light, temperature and iron availability (Moore et al, 1998;West and Scanlan, 1999;Johnson et al, 2006;Zwirglmaier et al, 2008;Rusch et al, 2010). It has been suggested that pangenome variability allows Prochlorococcus as a genus to proliferate across many environments (Partensky et al, 1999;Kettler et al, 2007), but it is unclear how the mechanisms of descent contribute to their evolution and the diversity of local populations.…”
Section: Introductionmentioning
confidence: 99%